2015
DOI: 10.1155/2015/170176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Factors on Germination and Emergence of Invasive Rumex confertus in Central Europe

Abstract: Rumex confertus is a biennial species native to Eastern Europe and Asia, where it thrives on meadow-steppes and glades in forest-steppe. This species has increased its range rapidly within central Europe, yet its biology is not well understood, which has led to poorly timed management. Effects of temperature, light, sodium chloride (NaCl), hydrogen ion concentration (pH), potassium nitrate (KNO3), and polyethylene glycol 6000 on seed germination were examined. Seedling emergence was examined for seeds sown at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…These results were obtained for some halophytes (Bajji et al 1998;Matoh et al 1986). Several studies demonstrate a significant decrease of seed germination in condition of high salinity for invasive plant species (El-Keblawy & Al-Rawai 2005;Kołodziejek & Patykowski 2015;Javaid et al 2018).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These results were obtained for some halophytes (Bajji et al 1998;Matoh et al 1986). Several studies demonstrate a significant decrease of seed germination in condition of high salinity for invasive plant species (El-Keblawy & Al-Rawai 2005;Kołodziejek & Patykowski 2015;Javaid et al 2018).…”
Section: Discussionsupporting
confidence: 52%
“…f. (Vieira et al 2010), Piper aduncum L. (Rocha et al 2005;Dousseau et al 2011), Crassocephalum crepioides (Benth.) S. Moore, Ageratum conyzioides L. (Yuan & Wen 2018), Rumex confertus L. (Kołodziejek & Patykowski 2015) and numerous other invasive plant species. But in contrast, Celastrus orbicularis Thunb.…”
Section: Discussionmentioning
confidence: 99%
“…This prevents seedlings from emerging too late and being killed by frost in autumn before reproduction [34]. Kołodziejek and Patykowski [35] reported that Rumex confertus Willd. Germination percentage and rate were significantly higher in light than in darkness.…”
Section: Seasonal Dormancymentioning
confidence: 99%
“…However, the effect of salinity could be mediated through specific ion toxicity and/or reduced soil osmotic potential (Munns 2002;Kranner and Seal 2013;Maucieri et al 2018). Polyethylene glycol has been used to simulate drought or water-stress during germination and plant growth (Kołodziejek and Patykowski 2015). Germination inhibition in PEG-treated seeds is attributed mainly to osmotic, D r a f t rather than ion-specific toxicity effects, which is usually attributed to salinity.…”
Section: Salsola Drummondiimentioning
confidence: 99%
“…Solutions with higher levels of PEG have higher negative water potentials (Money 1989;Munns 2002). Several studies have used PEG to simulate drought during germination in several species (Okçu et al 2005;Sidari et al 2008;Muscolo et al 2014;Cochrane et al 2015;Kołodziejek and Patykowski 2015;Cavallaro et al 2016). As PEG is a non-penetrating polymer, it affects seed germination through its osmotic effect (Munns 2002).…”
Section: Effects Of Maternal Salinity On Drought Tolerance At Differementioning
confidence: 99%